Building Livelihood Resilience through Participatory Action Research and a Circular Economy Model for Female-Headed Farming Households - Nining Sholikhah; Desi Tri Utami; Nuning Melianingsih; Chusna Cahya Marhaeni (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2026)
Background: Female heads of households in rural areas face economic vulnerability due to limited access to productive resources and high dependence on household food expenditures. In rural households, the potential of kitchen waste and yard land has not been managed in an integrated manner. Purpose of the Study: This article aims to analyze the implementation of a community service program based on a circular economy through the integration of native chicken (layer) farming, kitchen waste management, and micro-vegetable gardens for female heads of households. Methods: The community service program used a Participatory Action Research (PAR) approach, involving participants as active subjects in problem identification, action planning, implementation, and reflection. Data was collected through participatory observation, FGDs, interviews, questionnaires, and production records. Results: The results showed a Hen Day Production rate of 70–80%, additional income of Rp 180,000–Rp 390,000 per month, and savings on vegetable purchases of Rp 40,000–Rp 60,000 per month. The integration of activities formed a circular economy flow that strengthened household economic and food resilience.